Doing More with Less : How Can Brazil Foster Development While Pursuing Fiscal Consolidation? - Flamini, Valentina (IMF Working Papers; Working Paper ;, 2019)
Following a benchmarking exercise, we estimate the spending required to reach satisfactory progress in the Sustainable Development Goals in the health, education, and infrastructure sectors in Brazil. We find that there is room for savings in education (up to 1.5 percentage point of GDP) and health (up to 2.5 percentage points of GDP) without compromising the quality of services but additional investments for over 3 percent of GDP per year are needed to close large infrastructure gaps in roads, water, and electricity by 2030. Brazil can do more with less, but increasing efficiency of public spending will require substantial reforms.